2006
DOI: 10.1111/j.1365-2222.2006.02553.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic supplementation for the first 6 months of life on allergen‐ and vaccine‐specific immune responses

Abstract: In summary, although we did not see any consistent effects on allergen-specific responses, our study suggests that probiotics may have immunomodulatory effects on vaccine responses. The significance and clinical relevance of this need to be determined in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 36 publications
1
35
0
2
Order By: Relevance
“…The frequency of developing atopic dermatitis in the offspring's of pregnant mothers who received Lactobacillus GG was significantly reduced by 2, 4, and 7 years, by 50%, 44%, and 36% respectively [125][126][127]. Lactobacillus acidophilus strain was not able to produce same result in a different study suggesting the strain specificity [128]. Lactobacillus GG in combination with B. lactis during pregnancy and breastfeeding reduced the risk of atopic eczema and allergic sensitization in child [129], whereas a mixture of probiotics (Lactobacillus GG, L. rhamnosus LC705, B. breve, and Propionibacterium freudenreichii ssp.…”
Section: Probiotics and Allergy And Immune Responsementioning
confidence: 68%
“…The frequency of developing atopic dermatitis in the offspring's of pregnant mothers who received Lactobacillus GG was significantly reduced by 2, 4, and 7 years, by 50%, 44%, and 36% respectively [125][126][127]. Lactobacillus acidophilus strain was not able to produce same result in a different study suggesting the strain specificity [128]. Lactobacillus GG in combination with B. lactis during pregnancy and breastfeeding reduced the risk of atopic eczema and allergic sensitization in child [129], whereas a mixture of probiotics (Lactobacillus GG, L. rhamnosus LC705, B. breve, and Propionibacterium freudenreichii ssp.…”
Section: Probiotics and Allergy And Immune Responsementioning
confidence: 68%
“…3,[9][10][11] Pemberian probiotik ini bertujuan untuk mengembalikan komposisi normal mikrobiota usus, sehingga akan mengurangi gejala atopi. [12][13][14][15][16] Sampai saat ini belum diketahui bagaimana pengaruh probiotik terhadap kejadian atopi pada bayi lahir SS yang berasal dari keluarga yang tidak mempunyai riwayat atopi pada 6 bulan pertama kehidupan.…”
Section: Pendahuluanunclassified
“…[5][6][7][8] Sampai saat ini telah diketahui bahwa pemberian probiotik akan mempengaruhi respons imun, yaitu probiotik menimbulkan rangsangan imunomodulasi sistem imun saluran cerna dan juga akan meringankan gejala atopi pada anak yang menderita atopi. 12,13,15 Adanya probiotik pada mukosa dan epitel usus akan membentuk komponen bioaktif yang memproduksi sitokin dan kemokin. Peptidoglikan pada dinding probiotik berfungsi sebagai antigen yang selanjutnya akan terbentuk subset sel T, yaitu Th3 dan sel ini memproduksi TGF-β dan berperan sebagai supresi aktif yang menyebabkan timbulnya toleransi oral.…”
Section: Pembahasanunclassified
“…Although no allergy preventive effect was observed in some cohorts, an immune modulatory effect was detected [69]. Reduced TNF and IL-10 responses to house dust mite were found [70]. Boyle et al demonstrated that prenatal Lactobacillus GG supplementation during the last month of pregnancy reduced heat-killed LGG-induced CD4+T cell proliferation [71], although no allergy preventive effects were observed [72].…”
Section: What Are the Mechanisms Behind Probiotics In Allergy Preventmentioning
confidence: 99%